If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -5)(x + -7) = 0 Reorder the terms: (-5 + 2x)(x + -7) = 0 Reorder the terms: (-5 + 2x)(-7 + x) = 0 Multiply (-5 + 2x) * (-7 + x) (-5(-7 + x) + 2x * (-7 + x)) = 0 ((-7 * -5 + x * -5) + 2x * (-7 + x)) = 0 ((35 + -5x) + 2x * (-7 + x)) = 0 (35 + -5x + (-7 * 2x + x * 2x)) = 0 (35 + -5x + (-14x + 2x2)) = 0 Combine like terms: -5x + -14x = -19x (35 + -19x + 2x2) = 0 Solving 35 + -19x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + -2x)(7 + -1x) = 0Subproblem 1
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {2.5, 7}
| 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 | | [2x-6]-4=26 | | v^2=8v+2 | | 4*x=88 | | 3*x-18=2*x^2-18+x^2+3*x+9 | | 5x+12-4x-14=3 | | 5y-10+y+48=5y+40-1y | | 3m+5=2m+3 | | 5xy^2+2x^2+y^3=0 | | 2(t+5)=2 | | 12ab/a^2b^2/3b/2a | | 14-x+2x+5=180 | | h^2+18h+81=0 | | 16x(2)-8x=0 | | 3x+14=-31-6x |